Developing a Return to Work Intervention for Breast Cancer Survivors with the Intervention Mapping Protocol: Challenges and Opportunities of the Needs Assessment - Fassier, Jean-Baptiste; Lamort-Bouché, Marion; Broc, Guillaume; Guittard, Laure; Péron, Julien; Rouat, Sabrina; Carretier, Julien; Fervers, Béatrice; Letrilliart, Laurent; Sarnin, Philippe (Frontiers in Public Health, 2018)
Return to work (RTW) is an important step for breast cancer survivors (BCSs). However, they face many barriers that affect particularly women with low socioeconomic status (SES). Health care, workplace, and insurance actors lack knowledge and collaborate poorly. No intervention to date has proven effective to reduce social disparities in employment after breast cancer. The intervention mapping (IM) protocol is being used in France to develop, implement, and evaluate an intervention to facilitate and sustain RTW after breast cancer [FAciliter et Soutenir le retour au TRAvail après un Cancer du Sein (FASTRACS) project]. The research question of this study was to elicit the needs for RTW after breast cancer from various stakeholders’ point of view. The aim of this study was to describe the process and the preliminary results of the needs assessment of the FASTRACS project. Different methods were followed to (a) establish and work with a planning group and (b) conduct a needs assessment to create a logic model of the problem. A planning group was organized to gather the stakeholders with the research team. A review of the literature and indicators was conducted to identify the magnitude of the problem and the factors influencing RTW. A qualitative inquiry was conducted with 12 focus groups and 48 individual semi-structured interviews to explore the needs and experience of the stakeholders. The results of these tasks were the proposition of a charter of partnership to structure the participative process, a review of the scientific evidence and indicators, and the description by the stakeholders of their needs and experience. Many stakeholders disagreed with the concept of “early intervention.” They advocated for a better support of BCSs during their RTW, emphasized as a process. Anticipation, intersectoral collaboration, and workplace accommodation were mentioned to fit the needs of the BCS and their environment. A logic model of the problem was elaborated from these data. The ability of the model to consider specific characteristics of women with low SES is discussed, with a view to developing the FASTRACS intervention through the next steps of the IM protocol.